AB0/Rhesus Blood Group Does Not Influence Clinicopathological Tumor Characteristics or Oncological Outcome in Patients Undergoing Radical Prostatectomy - Oh, Su Jung; Mandel, Philipp; Chun, Felix K. H.; Tennstedt, Pierre; Peine, Sven; Hohenhorst, Jan Lukas; Hiller, Jens; Graefen, Markus; Tilki, Derya; Steuber, Thomas (Frontiers in Surgery, 2017)
Objectives AB0 blood group is an inherited characteristic that has been associated with the incidence as well as the prognosis of several malignancies. The aim of the current study was to clarify the role of the blood group in cancer epidemiology and clinical outcome of patients with prostate cancer (PCa). Methods Data from 3,574 patients undergoing radical prostatectomy between 2009 and 2010 at a single European institution were retrospectively analyzed. The correlation of AB0 and Rhesus blood group with PCa-related characteristics and oncological outcome were evaluated using univariable and multivariable Cox proportional hazard models. Results Median follow-up was 36.9 months. The overall distributions of AB0, as well as Rhesus blood groups among patients with PCa, did not differ from the distribution observed in the normal population. There was no significant association between AB0/Rhesus blood groups and Gleason score, prostate volume, surgical margin, pT-stage, pN-status, or preoperative prostate-specific antigen level. In multivariable Cox regression analysis, no statistically significant correlation between AB0/Rhesus group and biochemical recurrence was observed (all p > 0.05). Conclusion Our data suggest no relevant association of AB0/Rhesus blood group with adverse clinicopathological tumor characteristics or oncological outcome after surgery in contrast to several other malignancies.